2023
DOI: 10.1002/cbf.3782
|View full text |Cite|
|
Sign up to set email alerts
|

Ameliorative effect of sesame oil on experimentally induced polycystic ovary syndrome: A cross‐link between XBP‐1/PPAR‐1, regulatory proteins for lipogenesis/steroids

Abstract: Polycystic ovary syndrome (PCOS) is a mixed endocrine/metabolic/reproductive disorder in women of reproductive age. Sesame oil (SO) contains sesame lignans & vitamin E with broad-spectrum antioxidant and anti-inflammatory effects. This study investigates the ameliorative effect of SO on experimentally induced PCOS and elucidates the possible molecular mechanisms with a deeper focus on the different signaling pathways involved.The study was carried out on 28 nonpregnant female Wister albino rats that were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…Also, the microscopic examination of the ovarian cortex of PCOS rats revealed multiple cystic follicles in the ovarian cortex with markedly thin granulosa cell layer, vacuolated granulosa and theca cell layers, and desquamated granulosa cells. These findings followed several publications which reported that administering letrozole to female adult rats can cause PCOS similar to those seen in humans 6,34,35 …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Also, the microscopic examination of the ovarian cortex of PCOS rats revealed multiple cystic follicles in the ovarian cortex with markedly thin granulosa cell layer, vacuolated granulosa and theca cell layers, and desquamated granulosa cells. These findings followed several publications which reported that administering letrozole to female adult rats can cause PCOS similar to those seen in humans 6,34,35 …”
Section: Discussionsupporting
confidence: 85%
“…These findings followed several publications which reported that administering letrozole to female adult rats can cause PCOS similar to those seen in humans. 6,34,35 One fundamental aspect of PCOS is the disruption of steroid hormones. LH pulse frequency increases with high testosterone in female PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of aromatase activity in non-pregnant female rats is a well-established animal model for polycystic ovary syndrome (PCOS). The protective effects of sesame oil on these rats are mediated by the amelioration of regulatory proteins for ER stress, lipogenesis, and steroidogenesis through the PI3K/PKA or MAPK/ERK2 signaling pathway 29 . Therefore, the associations between the PI3K/PKA or MAPK/ERK2 pathway and aromatase level may be involved in the therapeutic effects of sesame oil on female-dominant diseases.…”
Section: Discussionmentioning
confidence: 99%